Proceedings of the International Conference on Banking, Accounting, Management, and Economics (ICOBAME 2018) 2019
DOI: 10.2991/icobame-18.2019.3
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and Elasticity of Labor Use on Economic Sectors in Indonesia

Abstract: The research objectives are: (1) to analyze the level of efficiency and elasticity of the use of labor in Gross Domestic Product (GDP) based on economic sectors in Indonesia in the period of 2010-2016, (2) to find out the changes/ transformations in the use of labor among the economic sectors in Indonesia in the period of 2010-2016. The analytical method used is a descriptive and analytical method of the Cobb-Douglass production function. The results showed that during the period of 2010-2016 there had been a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Efficiency is the relationship between resource inputs (costs, such as labor, capital, or equipment) and outputs (results or outcomes) [5]. Nababan [6] states that efficiency is a parameter for measuring company performance in the production process. Coelli et al [7] identified three types of efficiency: technical efficiency, allocative efficiency, and overall efficiency.…”
Section: Efficiencymentioning
confidence: 99%
“…Efficiency is the relationship between resource inputs (costs, such as labor, capital, or equipment) and outputs (results or outcomes) [5]. Nababan [6] states that efficiency is a parameter for measuring company performance in the production process. Coelli et al [7] identified three types of efficiency: technical efficiency, allocative efficiency, and overall efficiency.…”
Section: Efficiencymentioning
confidence: 99%